Electrochemical sensors of food colorant – Eosin Y dye on carbon nanomaterials modified glassy carbon electrode. (2022) - Dhasarathan, R.; Kavitha, B.; Aswathaman, H.; Senthilkumar, N.; Rani, S.
Abstract: The electrochemical activity of Eosin Y on the novel surface of carbon nanomaterials modified electrode was studied in the buffer media of different pH conditions by cyclic and differential pulse voltammetry. The pH 4.0 was selected as best for further studies. Cyclic voltammograms were recorded in the potential range from 0 V to −1.2 V. A well-developed voltammetric peak probably related to the cathodic reduction of carbonyl group was obtained in pH 4.0 acetate buffer at −0.6 V. An irreversibility nature of the reduction process was confirmed by cyclic voltammetric technique. The derived voltammetric sensor shows good electro catalytic activity to the reduction of eosin Y by giving elevated peak current at the modified electrode than those obtained for the bare electrode surface. At the optimized conditions, the cathodic peak current of eosin Y proportional to the concentration ranges between 50 ppb and 300 ppb with the limit of detection of 20 ppb by differential pulse voltammetry method. The developed electrode exhibited good selectivity, stability, repeatability, and has been successfully used to determine the real sample. The modified electrode surface stability was characterized by number of cycling method. The eosin Y dye adsorbed electrode surface behavior was studied by atomic force microscopy.